Toxicity of magnesium alloy biodegradation products in experiment - Yu. M. Neryanov; M. L. Golovakha; I.F. Belуеnіchev; V.N. Chorny; E.V. Yatsun (Zaporozhye State Medical University, 2013)
The article presents information on the study of possible toxic effects of biodegradation products of original magnesium-based alloy on laboratory rats. The used laboratory methods of investigation are described. Author has examined biochemical parameters of plasma on the base of which endogenous intoxication in rats was studied. It was found out that products of alloy biological resorption don't cause toxic effects on tissues and don't enhance cell destruction, that is evidenced by the absence of signs of endogenous intoxication and oxidative damage of functional macromolecules. Materials and methods. We used white mongrel male rats weighing 220-270 g (n = 20). Fixator consisting of a modified magnesium alloy ML-10 was implanted into the femur muscle mass of the animals of the experimental group (n = 14). The control group consisted of white mongrel male rats weighing 230-250 g (n = 6), which were not subjected to surgery (intact group). The degree of oxidative damage to proteins, the content of the average molecular weight, nucleic acids and the stable metabolites of nitric oxide were evaluated in plasma. Results and discussion. The studies revealed the reliable (relative to the intact group) increase in the content of all fractions of middle molecules in the plasma of the experimental group of rats, the increase shows only that the immune system of animals with magnesium implants is in a reactive state and responds with minor release of biologically active substances into the bloodstream. At this rate of endogenous intoxication this exponent usually increases tenfold, but we have not seen that. Levels of stable metabolites of nitric oxide increase insignificantly(1,4 times), that likely indicates more on the start of adaptive signaling processes than a pathological condition. The experimental data concerning the content of nucleic acids in the plasma of animals with magnesium implants testifies in support of this hypothesis. There were no significant differences in this index, so there is no reason to believe that the products of biodegradation of the implant provoke cell dying. For a more complete assessment of the pro- and antioxidant processes against the implanted clip in the body, we studied the degree of oxidative modification of proteins plasma. No significant differences in plasma levels of intact animals and experimental groups such as molecular markers: average mass, nucleic acid and the stable metabolites of nitric oxide have been received. Conclusion 1. It was established experimentally that products of modified magnesium alloy ML-10 biocorrosion did not have toxic effects on body tissues and didn't enhance cellular destruction, that was evidenced by the absence of endogenous intoxication signs and oxidative damage of functional macromolecules. 2. Gradual (for seven months) metabolization of metal fixator consisting of biodegradable magnesium alloy ML-10 in white mongrel male rats was accompanied by the absence of violations of physiological manifestations in experimental animals. 3. Better prognosis for the possibility of studying the use of metal fixators consisting of biodegradable magnesium alloy ML-10 in humans can be done on the base of the experiment results.